2012
DOI: 10.1128/jcm.05895-11
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Streptococcus pneumoniae Serotype 6D Clones in South Korea

Abstract: Streptococcus pneumoniae is a common and important pathogen that causes invasive and noninvasive bacterial diseases in infants, children, and adults. S. pneumoniae comprises more than 90 serotypes. Although serogroup 6 was classically considered to consist of serotypes 6A and 6B, another two serotypes, 6C and 6D, have recently been described (14,22). It has been postulated that serotypes 6C and 6D emerged by the replacement of wciN ␤ in the capsular loci of serotypes 6A and 6B, respectively (3, 22). However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…These results are higher than the 2011 domestic Streptococcus pneumoniae serotype epidemiological study [14], indicating that the carriage rate of 6D has increased. Regarding 6D, there is a study reporting that from the 3 sequence types (ST 189, 282, ST 3171), ST282 had high penicillin tolerance [21], but in this study, it was fortunately confirmed that all 3 sequence types have susceptibility to amoxicillin. In the non-vaccine type, the 34 serotype was isolated in 9 cases in the vaccinated group (3.3%) and in 4 cases in the non-vaccinated group (3.9%) showing the highest carriage rate in both groups, but again, it showed nearly no tolerance to amoxicillin.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…These results are higher than the 2011 domestic Streptococcus pneumoniae serotype epidemiological study [14], indicating that the carriage rate of 6D has increased. Regarding 6D, there is a study reporting that from the 3 sequence types (ST 189, 282, ST 3171), ST282 had high penicillin tolerance [21], but in this study, it was fortunately confirmed that all 3 sequence types have susceptibility to amoxicillin. In the non-vaccine type, the 34 serotype was isolated in 9 cases in the vaccinated group (3.3%) and in 4 cases in the non-vaccinated group (3.9%) showing the highest carriage rate in both groups, but again, it showed nearly no tolerance to amoxicillin.…”
Section: Discussionmentioning
confidence: 52%
“…However in vaccinated cases, there are results where Streptococcus pneumoniae reside as serotypes, which are not included in the vaccine, and problems of new serotypes with high tolerance have been posed; thus, clinical epidemiological research such as those above should be continuously conducted in young children [15-18]. Through Streptococcus pneumoniae serotypes isolated through such studies and antimicrobial sensitivity results, information should be continuously provided to primary care physicians to help them choose the most effective oral antimicrobials [19-21]. In addition, Korea has the highest tolerance rate of penicillin for this bacterium in the world, so this kind of epidemiological study is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…ST3171 was registered only in South Korean isolates of serotype 6B (n = 3) and 6D (n = 1) Eun et al, 2010;Song et al, 2011). The serotype 6D pneumococcal clone ST282 has been suggested to have emerged from the capsular switching between ST81 6A and ST3171 6D (Ko et al, 2012). A novel serotype 6C isolate with ST282, which was obtained from the nares of a 16-month-old healthy carrier, was identified in this study.…”
Section: Discussionmentioning
confidence: 95%
“…This serotype, designated S. pneumoniae serotype 6D, has been detected in both nasal carriage and invasive isolates (2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%